Does diet-induced weight loss lead to bone loss in overweight or obese adults? A systematic review and meta-analysis of clinical trials - Zibellini, J.; Seimon, R.; Lee, Crystal; Gibson, A.; Hsu, M.; Shapses, S.; Nguyen, T.; Sainsbury, A. (American Society for Bone and Mineral Research, 2015)
Diet-induced weight loss has been suggested to be harmful to bone health. We conducted a systematic review and meta-analysis (using a random-effects model) to quantify the effect of diet-induced weight loss on bone. We included 41 publications involving overweight or obese but otherwise healthy adults who followed a dietary weight-loss intervention. The primary outcomes examined were changes from baseline in total hip, lumbar spine, and total body bone mineral density (BMD), as assessed by dual-energy X-ray absorptiometry (DXA). Secondary outcomes were markers of bone turnover. Diet-induced weight loss was associated with significant decreases of 0.010 to 0.015 g/cm2 in total hip BMD for interventions of 6, 12, or 24 (but not 3) months' duration (95% confidence intervals [CIs], -0.014 to -0.005, -0.021 to -0.008, and -0.024 to -0.000 g/cm2, at 6, 12, and 24 months, respectively). There was, however, no statistically significant effect of diet-induced weight loss on lumbar spine or whole-body BMD for interventions of 3 to 24 months' duration, except for a significant decrease in total body BMD (-0.011 g/cm2; 95% CI, -0.018 to -0.003 g/cm2) after 6 months. Although no statistically significant changes occurred in serum concentrations of N-terminal propeptide of type I procollagen (P1NP), interventions of 2 or 3 months in duration (but not of 6, 12, or 24 months' duration) induced significant increases in serum concentrations of osteocalcin (0.26 nmol/L; 95% CI, 0.13 to 0.39 nmol/L), C-terminal telopeptide of type I collagen (CTX) (4.72 nmol/L; 95% CI, 2.12 to 7.30 nmol/L) or N-terminal telopeptide of type I collagen (NTX) (3.70 nmol/L; 95% CI, 0.90 to 6.50 nmol/L bone collagen equivalents [BCEs]), indicating an early effect of diet-induced weight loss to promote bone breakdown. These data show that in overweight and obese individuals, a single diet-induced weight-loss intervention induces a small decrease in total hip BMD, but not lumbar spine BMD. This decrease is small in comparison to known metabolic benefits of losing excess weight.